Próba oceny skuteczności terapii BEMER w procesie odnowy biologicznej po wysiłku wytrzymałościowym i wybranych funkcjach poznawczych. Opis przypadku - Mrozkowiak, Mirosław; Mrozkowiak, Magdalena (Journal of Education, Health and Sport, 2015)
Mrozkowiak Mirosław, Mrozkowiak Magdalena. Próba oceny skuteczności terapii BEMER w procesie odnowy biologicznej po wysiłku wytrzymałościowym i wybranych funkcjach poznawczych. Opis przypadku = An attempt to evaluate the effectiveness of BEMER therapy wellness process after endurance exercise and cognitive functions selected. Case study. Journal of Education, Health and Sport. 2015;5(9):11-62. ISSN 2391-8306. DOI10.5281/zenodo.29904 http://dx.doi.org/10.5281/zenodo.29904 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A11-62 https://pbn.nauka.gov.pl/works/615733 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.07.2015. Revised 24.08.2015. Accepted: 24.08.2015. Próba oceny skuteczności terapii BEMER w procesie odnowy biologicznej po wysiłku wytrzymałościowym i wybranych funkcjach poznawczych. Opis przypadku An attempt to evaluate the effectiveness of BEMER therapy wellness process after endurance exercise and cognitive functions selected. Case study 1Mirosław Mrozkowiak, 2Magdalena Mrozkowiak 1Uniwersytet Kazimierza Wielkiego, Instytut Kultury Fizycznej, ul. Ogińskiego 16, 85-092 Bydgoszcz 2Bioergonsport, Nowa Biała k/Płocka Słowa kluczowe: BEMER, odnowa biologiczna, wytrzymałość, cechy krwi, funkcje poznawcze. Streszczenie Wstęp. Głównym rdzeniem technologii BEMER (Bio- Elektro- Magnetishe Energie – Regulation lub bioelektromagnetyczna regulacja energii) jest wielowymiarowa struktura sygnału, która ma skutecznie stymuluje ograniczone lub zaburzone mikrokrążenia. Celem badań jest ocena przydatności terapii BEMER w procesie odnowy biologicznej i funkcji poznawczych po wysiłku wytrzymałościowym. Metoda i materiał. Badany mężczyzna realizujący zdrowy styl życia poddał się oznaczeniu 46 wybranych wskaźników krwi w dwóch edycjach pomiarów po wysiłku wytrzymałościowym w czasie restytucji wspomaganej terapią BEMER. Uzyskane wyniki. Najbardziej znaczące zmiany zaobserwowano we wskaźnikach krwi: EOS%, HHb, cHCO3, PO2, SO2(c), O2Hb, COHb, BE, BEakt, EOS, NEU%, LYM%, BASO%, MONO%, tHb, cHCO3, BB, MeHb, WBC, RBC, insulinie i kortyzolu, HGB, MCV, RDW, MPV i PLT, tHb, SO2 (c), O2Hb, COHb i HHb. Wnioski. (1) Zastosowana metodyka terapii i profil parametrów sygnału BEMER poprzez zwiększenie światła naczyń mikrokrążenia wpływa zróżnicowanie na wielkość wybranych wskaźników krwi. Przy czym wielkości wielu mierzonych cech krwi są znacznie korzystniejsze w drugiej niż w pierwszej edycji badań, podczas której nie stosowano stymulacji, (2) Zastosowanie stymulacji BEMER w odnowie biologicznej po wysiłkach wytrzymałościowych u mężczyzn w 5-6 dekadzie życia może być uzasadnione. Uzyskane jednostkowe wyniki z przeprowadzonych pomiarów, nie mogą być podstawą do uogólnionych wniosków nad stosowaniem sygnału BEMER w ramach odnowy biologicznej po wysiłku wytrzymałościowym. Mogą być jedynie próbą wskazania kierunku dalszych dociekań nad modyfikacją metodyki stosowania i parametrów wielowymiarowego strukturalnie sygnału BEMER i intensyfikacją odnowy biologicznej po różnych wysiłkach, (3) Stwierdzono znaczący wpływ obciążenia wytrzymałościowego na funkcje poznawcze, w przeciwieństwie do sygnału BEMER, (4) Następujące cechy ze względu na brak istotnych zmian pod wpływem stymulacji bioelektromagnetycznej należy wyeliminować: K, Ca, Mg, WBC, NEU, LYM, NEU%, LYM%, cHCO3, MONO, PCT, PCO2, MCH, MCHC i funkcje poznawcze, a w to miejsce poddać analizie wybrane cechy moczu: sód, potas, chlorki, azot, hemoglobinurię, siarczany, amoniak i kreatyninę. Keywords: BEMER, wellness, strength, blood characteristics, cognitive functions. Abstract Admission. The main core technology BEMER (Bio Energie Elektro Magnetishe - Regulation or bioelektromagnetyczna energy adjustment) is a multi-dimensional signal structure, which has effectively stimulates restricted or impaired microcirculation. The aim of the study was to evaluate the usefulness of BEMER therapy in the wellness and cognitive function after exercise endurance. The method and material. Tested man pursuing a healthy lifestyle surrendered to the determination of 46 selected indicators of blood in two editions measurements after exercise endurance during restitution assisted therapy BEMER. Obtained results. The most significant changes were observed in the indices of blood EOS%, HHb, cHCO3, PO2, SO2(c), O2Hb, COHb, BE, BEact, EOS, NEU%, LYM%, BASO%, MONO%, tHb, cHCO3, BB, MeHb, WBC, RBC, insulin and cortisol, HGB, MCV, RDW, MPV, PLT, tHb, SO2 (c), O2Hb, COHb and HHb. Conclusions. (1) Methodology therapy and profile parameters BEMER signal by increasing the light microvascular variation affects the size of selected indicators of blood. When the size of a number of measured characteristics of blood are much better in the second than in the first round of the study, during which no stimulation is used, (2) Pacing BEMER in rejuvenating the effort strength in men 5-6 decade of life can be justified. Separate results obtained from the measurements can not be the basis for generalized conclusions on the use of the BEMER signal in the context of wellness after exercise endurance. They can only be an attempt to indicate the direction of future research on the modification methodology of application and performance of multi-dimensional structurally signal BEMER and intensification of wellness through various efforts, (3) Found a significant impact load endurance on cognitive function, as opposed to the signal BEMER (4) The following features from Due to the lack of significant changes under the influence of bioelectromagnetic stimulation should be eliminated: K, Ca, Mg, WBC, NEU, LYM, NEU%, LYM%, cHCO3, MONO, PCT, PCO2, MCH, MCHC and cognitive function, and the place to be analyzed selected features of urine sodium, potassium, chlorides, nitrates, hemoglobinuria, sulfates, ammonia, and creatinine.